2012
DOI: 10.1111/codi.12045
|View full text |Cite
|
Sign up to set email alerts
|

The role of biologics in pelvic floor surgery

Abstract: The advent of laparoscopic surgery and with it Laparoscopic Ventral Mesh Rectopexy (LVMR) has revolutionised the management of internal ⁄ external rectal and vaginal vault prolapse. These procedures have traditionally been performed with synthetic meshes. Biologics have gained a prominent role over the last decade in LVMR as well as perineal procedures for rectocoele and cystocoele repair. We examine the existing literature on the use of biologics in pelvic floor surgery comparing this with literature on synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…Perineal and transabdominal approaches have been proposed for the surgical treatment of patients with a rectal prolapse [5]. The abdominal approach is associated with better outcome and lower recurrence rate, but higher mortality, and the recent introduction of a laparoscopic approach has reduced postoperative complications and the length of hospital stay [6]. Laparoscopic rectopexy is the most commonly used transabdominal surgical technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perineal and transabdominal approaches have been proposed for the surgical treatment of patients with a rectal prolapse [5]. The abdominal approach is associated with better outcome and lower recurrence rate, but higher mortality, and the recent introduction of a laparoscopic approach has reduced postoperative complications and the length of hospital stay [6]. Laparoscopic rectopexy is the most commonly used transabdominal surgical technique.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic mesh is much more widely used than biological mesh during a rectopexy, but no consensus regarding which type of mesh to use has been achieved [6]. Mesh-related pelvic structures erosion after rectopexy has been described in the literature [2], but data on the incidence of erosion based on the mesh type are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Our observations suggest that surgeons' increased familiarity with APs (both open operations and laparoscopy) might be associated with lower recurrence. Some studies [20,21] suggested that the learning curve for AP might be responsible for recurrences. In the PP group, the recurrence rates are consistent with the rates that have been reported previously: 0%-20% for Altemeier's procedure [22], and 4%-38% for Delorme's procedure [11].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of published data show functional improvement in terms of FI (4-91 %), constipation (37-86 %) [2,3,5,6] and dyspareunia and sexual dysfunction (39 %) [6] for patients with internal and external RP treated with LVR. These functional outcomes are usually obtained using synthetic mesh for rectal suspension which has been shown to increase the efficacy of the reconstructive procedure while reducing the recurrence rate by 30 % [7], compared with pexies without mesh.…”
Section: Introductionmentioning
confidence: 99%